Subscription Page (The Review of Asset Pricing Studies, 2013)
Subscription Page Get access The Review of Asset Pricing Studies, Volume 3, Issue 1, June 2013, Page i3, https://doi.org/10.1093/rapstu/ras022 Published: 03 May 2013